Behavior of ECC-encased CFST columns under axial compression. (15th September 2018) - Cai, Jingming; Pan, Jinlong; Li, Xiaopeng
Highlights: The ECC-encased CFST column was proposed in this paper. The proposed composite columns showed both high strength and ductility. The influence of different parameters were discussed. A new calculation method was proposed and verified. Abstract: This paper presents an experimental study on the mechanical behaviors of engineered cementitious composite (ECC)-encased concrete filled steel tube (CFST) columns under axial loading. Six specimens, including four ECC-encased CFST columns and two concrete-encased CFST columns were tested. According to the test results, ECC-encased CFST columns showed both higher loading carrying capacity and more ductile behavior. The influence of longitudinal reinforcement ratio, stirrup ratio and the thickness of steel tube were discussed in this paper. Furthermore, a new method to calculate the carrying capacity of ECC-encased CFST columns was proposed and verified with experimental results.